The Impact of Mediated Teaching on Secondary School Students’ Academic Achievement in Social Studies: A Study in Ogun State, Nigeria - Olubela, Afolabi; Iyunade, Olufunmilayo (The Indonesian Institute of Science and Technology Research, 2025)
This study therefore determined the effects of mediated teaching on secondary school students’ academic achievement in social studies in Ogun state. A pretest, posttest, control group quasi-experimental design was employed for the study. Six secondary schools (public and private) in Ogun State were randomly selected. Two instruments were used for data collection, are Social Studies Academic Achievement Test and the Mediated Teaching Academic Achievement Questionnaire. The hypotheses were tested using Analysis of Covariance at 0.05 level of significance. Treatment has a significant effect on students’ achievement (F(2,110) = 17.269 P<0.05). This means that there is a significant difference in the achievement of students exposed to teaching with instructional resources than those students taught without instructional resources. It was recommended that government, school authorities, and other stakeholders should provide enough instructional resources for teaching and learning. Where the resources are unavailable or insufficient, teachers are encouraged to improvise.